Effectiveness of the Petiveria alliacea (mapurite) plant infusion on the evolution of the malignant melanoma in C57BL/6 mice (Gaceta de Ciencias Veterinarias, 2017)
The present work is defined as a descriptive study supported by non experimental field research, whose With the aim to determine the effectiveness of the P. alliacea (mapurite) plant infusion on the evolution of malignant melanoma in C57BL/6 mice, 64 mice were distributed in three groups: Control Melanoma, Preventive Treatment and Curative Treatment. 100,000 melanocytic cells were inoculated subcutaneous in the paw pad. Mapurite infusion was prepared at 1% and administered ad libitum, starting 15 days prior to inoculation in the Preventive and at the moment of inoculation in the curative group. Results shown that females survival was significantly higher in the groups treated with P. alliacea. In males no statistically significant differences were observed for mean survival time, however, 20% of the Preventive group survived more than 60 days. In terms of weight, statistically significant differences between groups were obtained in males, where 100% of those in the Control group, 64% in the Preventive group and 55% in the Curative group lost weight. In both females and males, the tumor increased significantly, however, in the male Preventive group, tumors were smaller at the third and fourth weeks, with a statistically tendency to significance. In conclusion, P. alliacea infusion increased survival and decreased lost weight and tumor growth, which suggest that mapurite could be used as an adjuvant in the treatment of malignant melanoma.
Keywords: P. alliacea; mice C57BL/6; melanotic cells; cancer; mapurite